Evaluación del aporte de gallinaza fresca en el rendimiento del cultivo de maíz (Zea mais) variedad Iniap 122, en dosis diferentes, en la parroquia Malchinguí, cantón Pedro Moncayo, provincia pichincha - Badillo Herrera, Adriana Elizabeth (2016)
This research was conducted in the parish Malchinguí Canton Pedro Moncayo, Pichincha Province, where the main crop is corn developed both in production to tender to dry. Monoculture, excessive use of synthetic fertilizers, among others have led to have very low yields of this crop at the sector level. For the aspects discussed above, this research was developed as an alternative, evaluating new varieties and management alternatives. The objectives of this pilot study were the following: Determine the performance of the production of white corn for tender of the INIAP 122 variety through the application of different treatments. To determine the effect of four doses of fresh manure on the vegetative growth of the maize variety INIAP 122. Perform economic analysis of the treatments used in the crop. To meet the above using 4 different doses of fresh manure compared to absolute control was raised. The experimental design was design "Full Boques Random" with 5 treatments and 3 repetitions, for a total of 15 experimental units, each unit had 20 m2 doses: fresh Gallinaza T1, T2 Gallinaza fresh, fresh Gallinaza T3, T4 Fresh manure applications 5,000, 10,000, 20,000, 40,000 kilograms per hectare respectively an absolute control over T0, constituting 300 m2 useful test surface. The variables were evaluated: emergency percentage, plant height to 30, 60 and 90 days, up to the flag leaf height insertion of ear, ear number per plant, days to harvest tender, weight average cob, cob length, number of rows per ear, number of kernels per row, tender grain yield and profitability. Economic analysis for the determination of net income and expenses that were used to determine the cost / benefit ratio was performed. The results were: The emergence percentage was on average 93%. For the variable plant height, the higher the T4 treatment up to 204.76 cm flag leaf. The height of insertion of ear, as was treatment with T4 120.02 cm. The number of ears per plant, were the major T1, T2, T3 treatments and T4 1 ear 2 ears. For the variable days to harvest tender, it was performed 148 days after planting. In the variable weight of the ears, the largest were the treatments T4 and T2 175.23 gr 173.68 gr. In the variable length of the ears, the greater were the T2 and T3 treatments with 15.75 cm, 15.74 cm. For the number of rows per ear, the largest were the treatments T3 and T2 10.46 10.26 rows and rows. For the number of kernels per row no significant differences was averaging 16.6 grains. For grain yield in tender (Corn), they were older treatments T4 with 13,186 kg / ha and T2 with 11,758 kg / Ha. The T1 treatment has a higher net benefit with a value of $ 2.336.56 and treatment cost $ 833.00 with a positive cost benefit ratio of 2.80, which indicates that it is the best alternative for the farmer compared with the control. The conclusions were: As to the variable height of the plant at 30, 60, flag leaf 90 days and it was observed that the treatments T3 and T4 and the highest peak was the lowest treatment T0. The yield tender kg / ha / cycle was observed that the T2 and T4 treatments had higher performance, while treatment T0 was the lowest. The recommendations were promoted acquire certified to have a high percentage of emergence, greater seed production; It is also appropriate to apply the manure at least 4 to 6 weeks before planting, in order to decompose and reduce its phytotoxicity problems. It should be considered soil analysis as much as manure and nutritional requirements of corn to be planted, so as not to use high doses of chicken manure on the ground, as these can cause nutritional imbalances in the development of agronomic crop .